2022
DOI: 10.1155/2022/8334927
|View full text |Cite
|
Sign up to set email alerts
|

AI-Based Prediction of Capital Structure: Performance Comparison of ANN SVM and LR Models

Abstract: Capital structure is an integral part of the corporate finance that sources the funds to finance growth and operations. Managers always have to maintain value of the firm to be higher than the cost of capital in order to maximize the shareholders wealth. Empirical studies have used sources of finance like debt and equity as variables of capital structure. A choice between debt and equity finance analyzes the firm’s ability to perform under the financially constrained environment to attain the sustainable growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Recently, over 500,000 patients with implanted cardiac innovators were recognized as requiring a critical firmware upgrade owing to a security weakness that exposed their device to potential hacking [51]. This follows earlier incidents, such as the recall of the SymbiqTM Infusion System when it was revealed that unauthorized individuals could access and manipulate Hospira's smart pumps over a hospital network to adjust patients' doses [52].…”
Section: Literature Reviewmentioning
confidence: 97%
“…Recently, over 500,000 patients with implanted cardiac innovators were recognized as requiring a critical firmware upgrade owing to a security weakness that exposed their device to potential hacking [51]. This follows earlier incidents, such as the recall of the SymbiqTM Infusion System when it was revealed that unauthorized individuals could access and manipulate Hospira's smart pumps over a hospital network to adjust patients' doses [52].…”
Section: Literature Reviewmentioning
confidence: 97%
“…There are two types of public-key encryption: asymmetrical and symmetrical [23]. It takes more computing power to encrypt with asymmetric encryption than symmetric encryption, but it is more secure [24]. Any information encryption and decoding methods used for testing IoMT…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to prior investigation, the business which is employed with the e-commerce supply chain depends on reliable access to a broadband connection [53]. Any network downtime and power outages could lead to serious issues in the entire supply chain [54]. To mitigate these issues, the service providers need to fix the reliability of the network and the connection [55], [56].…”
Section: Issues Related To Network Reliabilitymentioning
confidence: 99%